2016
DOI: 10.1016/j.str.2016.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Role of the PFXFATG[G/Y] Motif in the Activation of SdrG, a Response Regulator Involved in the Alphaproteobacterial General Stress Response

Abstract: Two-component systems are major signal transduction pathways, which consist of histidine kinases and response regulators that communicate through phosphorylation. Here, we highlight a distinct class of single-domain response regulators containing the PFXFATG[G/Y] motif that are activated by a mechanism distinct from the Y-T coupling described for prototypical receiver domains. We first solved the structures of inactive and active SdrG, a representative of the FAT GUY family, and then biochemically and genetica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(43 citation statements)
references
References 38 publications
5
38
0
Order By: Relevance
“…The precise mechanism and specific residues involved in this process merit further exploration. We further note that PhyR REC does not contain residues involved in the so‐called Y‐T coupling (Cho et al ., ) or FATGY (Campagne et al ., ) activation mechanisms and thus provides an excellent model to explore the diversity of REC domain signaling mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The precise mechanism and specific residues involved in this process merit further exploration. We further note that PhyR REC does not contain residues involved in the so‐called Y‐T coupling (Cho et al ., ) or FATGY (Campagne et al ., ) activation mechanisms and thus provides an excellent model to explore the diversity of REC domain signaling mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…3B). T220 is highly conserved and stabilizes the phosphoryl group in REC domains that utilize either Y-T coupling or FATGY signaling mechanisms (Cho et al, 2000;Sheftic et al, 2014;Campagne et al, 2016). This residue is required for conformational changes induced by BeF 2 3 modification in E. litoralis PhyR (Corrêa and Gardner, 2016).…”
Section: The Role Of Phosphorylation-induced Structural Changes In Phmentioning
confidence: 99%
“…A recent study had implicated the SDRR SdrG in the general stress response of the alpha-proteobacterium Sphingomonas melonis Fr1 (34). Sequence comparison revealed that SdrG and MrrA harbor a conserved PFXFATG(G/Y) motif that distinguishes these proteins from prototypical response regulators (35).…”
Section: Mrra Is a Central Phosphorylation Hub For Multiple Histidinementioning
confidence: 99%
“…In contrast to prototypical response regulators, MrrA lacks one of the residues involved in the Y-T coupling mechanism required for intramolecular signal transduction of Rec domains. Instead, it harbors the recently described FATGUY motif (35,51,52). Three other FATGUY response regulators are described, SdrG of S. melonis, Mext_0407 of Methylobacterium extorquens and Sma0114 of Sinorhizobium meliloti (34,53,54).…”
Section: Conserved and Divergent Roles Of Mrra In Alpha-proteobacteriamentioning
confidence: 99%
“…It remains unclear whether differences in the residues that catalyze phosphoryltransfer chemistry reflect higher order structural differences between HWE/HisKA2 and other HKs such as oligomeric state. Differences in catalytic residues may also be shaped by unique interactions between HWE/HisKA2 kinases and associated receiver domain substrates, such as those containing the so-called FATGY motif [28,29]. …”
Section: Biochemical Properties Of Hwe/hiska2 Kinasesmentioning
confidence: 99%